7 - Understanding Shifts in Nigeria’s Trade Policy: From Realism to Protectionism - Alayande, Folarin (Africa Development, 2020)
The reluctance of Nigeria, Africa’s largest economy, to sign two major international trade liberalisation agreements in 2018 shocked many local and international observers. However, these trade policy postures were not unexpected. Undiscerned by many analysts, many subtle changes had happened to Nigeria’s international co-operation architecture and foreign economic policy in a seemingly incoherent manner. In addition, the premise for expecting Nigeria to automatically consent to both agreements was faulty for two main reasons. First, the pretext of connectivity and market access as the underlying rationale for both agreements was allegedly hinged on the fallacy of composition, with the assumption that the whole was greater than the sum of its parts. This pretext was increasingly questioned by the influential, organised private sector in Nigeria, which had shifted from the altruistic foreign policy tenets of the 1970s to insulation from negative externalities of trade. Second, Nigeria’s trade posture was erroneously considered separately from its foreign economic policy posture, which was increasingly hinged on beneficial concentricism and regaining internal capabilities. In this new dispensation, with a focus on strategic trade policy underpinned by economic pragmatism, understanding shifts in the domestic balance of power is critical to predicting Nigeria’s trade policy responses.